Historicizing the present: Brussels attacks and heritagization of spontaneous memorials. Issue 1 (2nd January 2018) - Milošević, Ana
Abstract: This research article traces the process of transition from spontaneous to 'official' memorialisation of the 2016 Brussels terrorist attack by questioning which factors trigger the heritagization process of spontaneous memorials and their contents. With a view to critically assess the significance of heritage values in relation to terrorism, this article scrutinises how these values are grasped, narrated and articulated by the local authorities, government and archival institutions in the preservation, conservation and heritagization of spontaneous memorials. There is an emphasis on the two facets of heritagization: how meanings attached to a memorial and its objects are created and expressed by the community of bereavement, and how the transformation of places, practices, objects into diverse forms of 'heritage' evolves. This article brings a new perspective on the heritagization of spontaneous memorials, seen as important in determining how a traumatic event such is a terrorist attack will settle in the collective memory on the long term, by becoming historicized.